Synthesis of Lacosamide (Vimpat) and Its Derivatives from Aziridine-(2R)-carboxylate - Jeong, Hyeonsu; Yadav, Nagendra Nath; Ha, Hyun-Joon (Synthesis, 2017)
An efficient and scalable synthesis of the antiepileptic drug (R)-lacosamide and its derivatives has been achieved from commercially available aziridine-(2R)-carboxylate in three simple sequential steps, including regioselective aziridine ring opening, debenzylation followed by acetylation in one pot, and amide formation. The advantage of this protocol is that the starting material and reagents are commercially available and a single purification by recrystallization is required after all the chemical transformations, providing the final drug in >99.9% ee.
Keywords: (R)-lacosamide; Vimpat; antiepileptic drug; aziridine; regioselectivity